Sustainable Development’s Issues in the Light of Karol Wojtyła – John Paul II’s Political Philosophy and Theology - Ewertowski, Stefan; Modrzejewski, Arkadiusz (Problemy Ekorozwoju, 2013)
Philosophical and theological thought of Karol Wojtyła – John Paul II was also concerned with ecological issues. Generally, it is a part of his ethical and moral consideration, becoming important element of his political philosophy and theology. Personalistic hermeneutics is a key for understanding his sustainable development conception. It sees a fundamental criterion of ethical and moral evaluation of diverse forms of activity in human being. Firstly, pro-ecological activity means directing human being towards good. Pope John Paul II noticed many dangers for man and environment. He was convinced that whole international community should be involved in finding solutions.